І International Scientific Conference "National and international standards of a modern state: trends and prospects" (February 24, 2011, Kyiv) - Сопілко, Ірина Миколаївна; Великанова, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Current and important problems of state-building were published in the scientific reports of teachers and guests of the Law Institute, which aroused lively interest not only among scholars but also students. The participants of the conference came to the understanding that law-making in modern Ukraine testifies to the fact that, despite all the difficulties and misunderstandings, this process becomes forceful and inevitable.